Efforts to Prevent Anarchic Demonstrations Through Early Detection of Intelligence and Security Units in the Legal Territory of the Bekasi City Metro Police - Elyno Hizkia Sitorus (Police Studies Review, 2021)
The Indonesian people really appreciate the diversity of ethnic groups, religions, races, cultures, languages ​​and diverse individual characters. It is very possible for anarchic action to occur in the delivery of opinions. To overcome this, the State Police of the Republic of Indonesia needs to carry out its main duties and functions. This study aims to determine the efforts to prevent anarchic demonstrations through early detection of the Intelkam unit. In addition, this research is used to determine the factors that influence efforts to prevent anarchist demonstrations through early detection by the Intelkam unit. This research is a qualitative research that was conducted to understand the problem of non-conducive demonstrations in the city of Bekasi, which are seen to be significant. The researcher used descriptive analysis method. In obtaining information and data in this study, the authors used primary data and secondary data in this qualitative study. In this research, the researcher uses data triangulation to determine the accuracy of the data. The results showed that the Intelligence and Security Unit of the Bekasi Metro Police carried out intelligence activities by raising intelligence to prevent anarchic demonstrations that occurred in Bekasi City and were influenced by networks that had been placed in every community, such as students, mass organizations, and workers who increased material resources. precise and accurate information carried out according to the abilities and skills of each member through management measures. The factors that influence the implementation of efforts to prevent anarchic demonstrations through early detection by the Bekasi Metro Police Intelligence and Security Unit include unit strengths, unit weaknesses, opportunities for this there is the existence of intelligence networks that can provide information, and threats originating from the student environment. , mass organizations, and workers in provoking other people by being ridden by certain political elements to stage demonstrations. In this case, the leadership should be pleased with members of the Intelligence and Security Unit of the Bekasi City Police to strengthen intelligence gathering to increase trust building. Improve budget management and intelligence product creation, as well as improve coordination and motivation.